Sorting Nexin 5 Plays an Important Role in Promoting Ferroptosis in Parkinson's Disease. (5th May 2022) - Huang, Zifeng; Han, Jiajun; Wu, Peipei; Wu, Chunxiao; Fan, Yaohua; Zhao, Lijun; Hao, Xiaoqian; Chen, Dongfeng; Zhu, Meiling
Abstract : Parkinson's disease (PD) is a common neurodegenerative disease in the elderly, which is related to brain iron metabolism disorders. Ferroptosis is a newly discovered iron-dependent programmed cell death mode, which has been considered an essential mechanism of PD pathogenesis in recent years. However, its underlying mechanisms have not been fully understood. In the present study, the PD rat model and PD cell model were induced by 6-hydroyxdopamine (6-OHDA). The results showed that the expression of Sorting Nexin 5 (SNX5) and the level of ferroptosis will increase after treatment with 6-OHDA. Consistent with these results, ferroptosis inducer erastin synergistically reduced the expression of glutathione peroxidase 4 (GPX4) and increased the expression of SNX5 in the PD cell model, while ferroptosis inhibitor ferrostatin-1 (Fer-1) inhibited the decrease of GPX4 and the increase of SNX5 in the PD cell model. Knockdown of SNX5 in PC-12 cells could reduce intracellular lipid peroxidation and accumulation of Fe 2+ and significantly inhibit the occurrence of ferroptosis. In conclusion, the present study suggested that SNX5 promotes ferroptosis in the PD model, thus providing new insights and potential for research on the pharmacological targets of PD.